(untitled) (Malaysian Management Journal, 2008)
A hotel’s service delivery system is unique because it produces products as well as services. Priorresearch in this area is still scarce especially in the context of the Malaysian service industry. Thispaper investigates the extent of service delivery system practices in Malaysia’s hotels. In doing so, aquestionnaire was sent to all 474 star-rated hotels in Malaysia. A response rate of 19% was received.By using factor analysis and descriptive statistics, the results indicated that the extent of hotel servicedelivery system could be measured by the following seven dimensions – new products/services, customerparticipation, hotel operations layout, push/pull orientation, level of standardisation, use of InformationTechnology (IT), and human resource specialisation. Furthermore, on each dimension, managers ofhotels perceived that their hotels had high introduction of products/services, high customer participationfor service adaptation, mixed operations layout, pull orientation, high standardisation of processes, high use of IT for cost reduction, and low human resource specialisation.